D2 lymphadenectomy with complete mesogastrium excision vs. conventional D2 gastrectomy for advanced gastric cancer. Issue 10 (20th May 2022) - Meng, Xiangyu; Wang, Lu; Liu, Guangcong; Zhang, Jun; Wang, Yue; Yang, Dong; Zheng, Guoliang; Zhang, Tao; Zheng, Zhichao; Zhao, Yan
Abstract: Background: The complete mesogastrium excision (CME) based on D2 radical gastrectomy is believed to significantly reduce the local-regional recurrence compared with D2 radical gastrectomy in advanced gastric cancer, and it is widely used in China. This study aimed to explore whether D2 + CME is superior to D2 on surgical outcomes during gastrectomy from Chinese data. Methods: Feasible studies comparing the D2 + CME (D2 + CME group) and D2 (D2 group) published up to March 2020 are searched from electronic databases. The data showing surgical and complication outcomes are extracted to be pooled and analyzed. Results: Fourteen records including 1352 patients were included. The D2 + CME group had a shorter mean operative time (weighted mean difference [WMD] = —16.72 min, 95% confidence interval [CI]: −26.56 to −6.87 min, P   <  0.001), lower mean blood loss (WMD = −39.08 mL, 95% CI: −49.94 to −28.21 mL, P  < 0.001), higher mean number of retrieved lymph nodes (WMD = 2.13, 95% CI: 0.58–3.67, P  = 0.007), shorter time to first flatus (WMD = −0.31 d, 95% CI: −0.53 to − 0.10 d, P  = 0.005), and postoperative hospital days (WMD = −1.09, 95% CI: −1.92 to −0.25, P  = 0.010) than the D2 group. Subgroup analysis suggested that the advantages from the D2 + CME group were obvious in traditional open radical gastrectomy, proximal gastrectomy, and distal gastrectomy compared with D2 group. The evaluations of post-operative complications showed that the patients who underwent D2 + CME had a lower incidence of post-operative complications than the patients who underwent D2 surgery alone (relative risk [RR] = 0.65, 95% CI: 0.45–0.87, P  = 0.003). The D2 radical gastrectomy plus CME improved 3-year overall survival (OS) (RR = 1.16, 95% CI: 1.02–1.32, P  = 0.020) and lowered the local recurrence rate (RR = 0.51, 95% CI: 0.28–0.94, P  = 0.030). The patients undergoing laparoscopic surgery or total gastrectomy had more significant advantages compared between D2 + CME and D2 groups in 3-year OS. Conclusion: The data from China show that D2 radical gastrectomy plus CME are reliable procedures and safety compared to D2 radical gastrectomy with faster recovery, lower risk, and better prognosis.